Performance Analysis Of Certified Teachers Study At State Elementary School 7 Gorom Timur - Darlean, Salma; Latuapo, Ridwan; Rahman, Muhajirs Abd (Peneliti.net, 2025)
Study this aiming for analyze performance of certified teachers at SD 7 Negeri Gorom East in carrying out the learning process, and analyze factors that influence performance of certified teachers at SD Negeri 7 Gorom East as well as analyze efforts that can be made done for increase performance of certified teachers. Study this use method qualitative with approach studies case, with data collection through interviews, documentation, and observation as well as with 10 informants as subject research. Data analysis using data reduction, data presentation and conclusion. Data tested for data validity with testing credibility, transferability, dependability, and confirmability. Results study show that performance of certified teachers at SD Negeri 7 Gorom East. Performance of certified teachers at SD Negeri 7 Gorom East , in general overall show its performance Already Enough Good in aspect planning learning in a way overall . While performance of certified teachers at SD Negeri 7 Gorom East Still low in implementation learning. Because, learning is dominated by teachers and learning No relevant with RPP. While performance of certified teachers at SD Negeri 7 Gorom East in matter evaluation, already seen enough good; the indicator capable make instrument evaluation And do test daily, but teachers are lacking capable do process assessment and evaluation end learning. Can conclude , certified teacher Already Good on aspect planning learning but not yet optimal aspect implementation learning And process assessment and end learning .